High Iodine Induces the Proliferation of Papillary and Anaplastic Thyroid Cancer Cells via AKT/Wee1/CDK1 Axis - Lv, Chunpeng; Gao, Yanhui; Yao, Jinyin; Li, Yan; Lou, Qun; Zhang, Meichen; Tian, Qiushi; Yang, Yanmei; Sun, Dianjun (Frontiers in Oncology, 2021)
High iodine can alter the proliferative activity of thyroid cancer cells, but the underlying mechanism has not been fully elucidated. Here, the role of high iodine in the proliferation of thyroid cancer cells was studied. In this study, we demonstrated that high iodine induced the proliferation of BCPAP and 8305C cells via accelerating cell cycle progression. The transcriptome analysis showed that there were 295 differentially expressed genes (DEGs) in BCPAP and 8305C cells induced by high iodine, among which CDK1 expression associated with the proliferation of thyroid cancer cells induced by high iodine. Moreover, the western blot analysis revealed that cells exposed to high iodine enhanced the phosphorylation activation of AKT and the expression of phospho-Wee1 (Ser642), while decreasing the expression of phospho-CDK1 (Tyr15). Importantly, the inhibition of AKT phosphorylation revered the expression of CDK1 induced by high iodine and arrested the cell cycle in the G1 phase, decreasing the proliferation of thyroid cancer cells induced by high iodine. Taken together, these findings suggested that high iodine induced the proliferation of thyroid cancer cells through AKT-mediated Wee1/CDK1 axis, which provided new insights into the regulation of proliferation of thyroid cancer cells by iodine.